Perspective Lines System in A.S. Makarenko’s Pedagogical Experience - S. Nevskaja, S.; Mettini, E. (International Journal of Engineering and Technology, 2018)
In the paper is investigated perspective lines system created by A.S. Makarenko, are covered problems concerning psychological time and space, meaning of life, self-actualization, consciousness and self-awareness of individual. The individual perspective is regarded as an element of evolving self-awareness of former young offenders and homeless children. In human self-awareness, structure start evolving when there are representations of in the past, present and future. In the paper are provided insights into the connection of individual time perspective and individual morality, is proved that perspective lines system fulfills a very important function in defining moral value of man and that inside Makarenko’s collective individual developed in himself those qualities that helped to enter adult life worthy and find his place in community (society).